Corrosion control in the oil and gas industry - Papavinasam, Sankara, 1962- (Gulf Professional Pub., 2014)
This book provides engineers and designers with the tools and methods to design and implement comprehensive corrosion-management programs for oil and gas infrastructures. The book addresses all segments of the industry, including production, transmission, storage, refining and distribution.